Inhibition of Polyamine Uptake Potentiates the Anti‐Proliferative Effect of Polyamine Synthesis Inhibition and Preserves the Contractile Phenotype of Vascular Smooth Muscle Cells. Issue 6 (20th November 2015) - Grossi, Mario; Phanstiel, Otto; Rippe, Catarina; Swärd, Karl; Alajbegovic, Azra; Albinsson, Sebastian; Forte, Amalia; Persson, Lo; Hellstrand, Per; Nilsson, Bengt‐Olof
Abstract : Increased vascular smooth muscle cell (VSMC) proliferation is a factor in atherosclerosis and injury‐induced arterial (re) stenosis. Inhibition of polyamine synthesis by α‐difluoro‐methylornithine (DFMO), an irreversible inhibitor of ornithine decarboxylase, attenuates VSMC proliferation with high sensitivity and specificity. However, cells can escape polyamine synthesis blockade by importing polyamines from the environment. To address this issue, polyamine transport inhibitors (PTIs) have been developed. We investigated the effects of the novel trimer44NMe (PTI‐1) alone and in combination with DFMO on VSMC polyamine uptake, proliferation and phenotype regulation. PTI‐1 efficiently inhibited polyamine uptake in primary mouse aortic and human coronary VSMCs in the absence as well as in the presence of DFMO. Interestingly, culture with DFMO for 2 days substantially (>95%) reduced putrescine (Put) and spermidine (Spd) contents without any effect on proliferation. Culture with PTI‐1 alone had no effect on either polyamine levels or proliferation rate, but the combination of both treatments reduced Put and Spd levels below the detection limit and inhibited proliferation. Treatment with DFMO for a longer time period (4 days) reduced Put and Spd below their detection limits and reduced proliferation, showing that only a small pool of polyamines is needed to sustain VSMC proliferation. Inhibited proliferation by polyamine depletion was associated with maintained expression of contractile smooth marker genes. In cultured intact mouse aorta, PTI‐1 potentiated the DFMO‐induced inhibition of cell proliferation. The combination of endogenous polyamine synthesis inhibition with uptake blockade is thus a viable approach for targeting unwanted vascular cell proliferation in vivo, including vascular restenosis. J. Cell. Physiol. 231: 1334–1342, 2016. © 2015 Wiley Periodicals, Inc.